Construction of Shoot Apical Meristem cDNA Yeast Library of Brassica napus L. and Screening of Proteins That Interact with the Inflorescence Regulatory Factors BnTFL1s - Lingxiong Zan; Haidong Liu; Xutao Zhao; Dezhi Du; Kaixiang Li (Current Issues in Molecular Biology)
The determinate inflorescence trait of Brassica napus L. is associated with various desirable agricultural characteristics. BnTFL1s (BnaA10.TFL1 and BnaC09.TFL1), which encode the transcription factor TERMINAL FLOWER 1 (TFL1), have previously been identified as candidate genes controlling this trait through map-based cloning. However, the mechanism underlying the effects of the BnTFL1 proteins remains unclear. Further, proteins generally interact with each other to fulfill their biological functions. The objective of this study was to construct a cDNA library of the shoot apical meristem (SAM) of B. napus and screen for proteins that interact with BnTFL1s, to better understand its mechanism of action. The recombination efficiency of the yeast two-hybrid (Y2H) library that we constructed was 100%, with insertion fragment lengths ranging from 750 to 2000 bp and a capacity of approximately 1.44 × 107 CFUs (colony-forming units), sufficient for screening protein interactions. Additionally, the bait vector pGBKT7-BnTFL1s was transformed into yeast cells alongside positive and negative controls, demonstrating no toxicity to the yeast cells and no self-activation. This bait was used to screen the SAM cDNA library of B. napus, ultimately identifying two BnTFL1s-interacting proteins: 14-3-3-like protein GF14 omega GRF2. These interactions were verified through one-to-one interaction experiments. This study provides a foundation for further research on the biological functions of the BnTFL1s genes and their regulatory role in inflorescence formation in B. napus, while providing a reference for studying similar mechanisms in other plants.